MOLECULAR GAS PROPERTIES IN LOCAL LUMINOUS INFRARED GALAXIES - Sliwa, Kazimierz (My University, 2015)
In this thesis, I analyze the physical conditions such as temperature, volume density and column density of the molecular gas in four Luminous Infrared Galaxies (LIRGs): Arp 55, NGC 1614, VV 114 and NGC 2623. LIRGs are systems where two gas-rich galaxies are in the process of merging. The goal of my thesis is to look for trends in the molecular gas properties during the merger process. I use several observations of transitions of carbon monoxide (12CO) and its isotopologue 13CO from the Submillimeter Array, Combined Array for Research in Millimeter-wave Astronomy and Atacama Large Millimeter/submillimeter Array. The high-resolution observations allow me to analyze the molecular gas at several positions inside a single galaxy. The observations are fitted to models obtained from a radiative transfer code using a Bayesian likelihood method. I find that advanced mergers such as NGC 2623 and VV 114 have warmer (≥40 K), less dense (≤ 10^3 cm^−3) molecular gas than early/intermediate stage mergers such as Arp 55 and NGC 1614. I suggest that there are mechanisms such as stellar winds, supernovae and AGN activity that dissipate the molecular gas and thus lower the density and warm the gas as the merger progresses. The molecular gas pressure of the advanced mergers is found to be lower by nearly an order of magnitude when compared to the early/intermediate stage mergers. I also find that the [12CO]/[13CO] abundance ratio in NGC 1614, VV 114 and NGC 2623 is unusually high (> 100) when compared to the interstellar medium value near the center of the Milky Way (∼ 30). Interestingly, Arp 55 does not conform to this trend with a [12CO]/[13CO] value of ∼ 30, similar to the Milky Way center. I suggest that nucleosynthesis may play a big role in enhancing the abundance ratio and/or the molecular gas from the outer radii of Arp 55 has not reached the central inner regions to drive the abundance ratio up. Nevertheless, Arp 55 is in an interesting merger stage. Finally, I measured the CO luminosity to molecular gas mass conversion factor, alpha_{CO}, across the sample in search of the transition stage from a Galactic-like alpha_{CO} to the 4-5 times lower value found in LIRGs. iii The four sources all have measured alpha_{CO} values that are consistent with the LIRG value of 0.8 M_{sol} (K km s^−1 pc^2)^−1. I suggest that we look at an even earlier merger stage such as Arp 240 to find the point of transition. With the golden age of submillimeter astronomy upon us, this is just the beginning of furthering our knowledge of the merger process and what happens to the molecular gas, the fuel for all star formation.
Keywords: Submillimeter Astronomy, Molecular Gas, Interacting Galaxies, Luminous Infrared Galaxies, Radiative Transfer